2010
DOI: 10.1289/ehp.0901412
|View full text |Cite
|
Sign up to set email alerts
|

137 Cesium Exposure and Spirometry Measures in Ukrainian Children Affected by the Chernobyl Nuclear Incident

Abstract: BackgroundAfter the Chernobyl accident in 1986, children of the contaminated Narodichesky region of Ukraine were obliged to participate in a yearly medical screening. They have been exposed to 137cesium (137Cs; half-life = 30 years) in contaminated soils, air, and food.ObjectiveUsing a “natural experiment” approach and a longitudinal prospective cohort study design, we investigated the association of soil 137Cs and spirometry measures for 415 children using 1,888 repeated measurements from 1993 to 1998.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Certainly, some investigators previously have suggested that the observed recurring fluctuations in cytokine expression are due to disruptions in communication between responding infiltrating cells and the damaged cells in the irradiated microenvironment, resulting in compromise of the immune response (Schaue & McBride 2010). In addition, the clinical outcomes from events such as Chernobyl, Tokai-mura, and others would suggest that, when the lung is injured as part of a whole body exposure, the level of pulmonary toxicity expressed are exacerbated by the systemic injury (Goans & Wald 2005, Vlasov & Kvacheva 1996, Svendsen et al 2010, Uozaki et al 2005). This observation is supported by data from the bone marrow transplant literature, where acute respiratory distress syndrome/late pneumonitis are relatively common, and frequently lethal, outcomes (Cooke 2005, Ortonne et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, some investigators previously have suggested that the observed recurring fluctuations in cytokine expression are due to disruptions in communication between responding infiltrating cells and the damaged cells in the irradiated microenvironment, resulting in compromise of the immune response (Schaue & McBride 2010). In addition, the clinical outcomes from events such as Chernobyl, Tokai-mura, and others would suggest that, when the lung is injured as part of a whole body exposure, the level of pulmonary toxicity expressed are exacerbated by the systemic injury (Goans & Wald 2005, Vlasov & Kvacheva 1996, Svendsen et al 2010, Uozaki et al 2005). This observation is supported by data from the bone marrow transplant literature, where acute respiratory distress syndrome/late pneumonitis are relatively common, and frequently lethal, outcomes (Cooke 2005, Ortonne et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Considering I-131, Cs-134, and Cs-137, with half-life of 8.05 days, 2.06 years, and 30.1 years [21,22], respectively, cesium will have a larger health impact in the future. Svendsen et al reported an increase in respiratory diseases after a nuclear power plant accident because dust with high cesium concentrations from the soil can often be inhaled [23]. Wearing a mask is considered to be effective to prevent dust inhalation, and one way to prevent ingestion of radioactive materials is to avoid outdoor eating and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this is a dynamic cohort since not all children participated in all years; new children entered and older ones left the cohort due to reaching adulthood. The cohort is described in detail elsewhere [13,20]. The dynamic cohort …”
Section: Study Populationmentioning
confidence: 99%